Plant-based mucilage with healing and anti-inflammatory actions for topical application: A review - Oliveira Filho, Josemar Gonçalves de [UNESP]; Lira, Michelle Monteiro; Sousa, Tainara Leal de; Campos, Stéphani Borges; Lemes, Ailton Cesar; Egea, Mariana Buranelo (Elsevier, 2021)
The profile of consumers has changed over the years, and the number of people who have adhered to the vegan and vegetarian lifestyle, focused on the consumption, and use of plant-based products, has increased considerably including the use of products for wound care. A wound is a type of injury that occurs on healthy skin and the recovery process can represent a health concern worldwide. The materials used for topical application play an important and crucial role in the process of rapid healing and protection. The development of healing materials with good properties and meet the new demands of the consumer market is a major challenge for the pharmaceutical industry. Plant-based mucilage for topical application as dressing or cream to wound healing can offer an alternative for these diverse consumers and thus has received great attention in recent decades. This approach is an ecologically correct concept that maintains a moist environment, minimizes healing time, and reduces (or considerably prevents) infections. This review highlights plant-based mucilage that may or may not form a film (used as a dressing or a cream) and can be used for topical application due to demonstrated anti-inflammatory or healing properties. In this text, we focus only on plant-based mucilage from Abelmoschus esculentus, Aloe vera, Linum usitatissimum, Pereskia aculeata, and Salvia hispânica L. which can be used to match the requirements of minimalist; vegan, vegetarian, or plant-based; and sustainable and agroecological lifestyles.
Keywords: Aloe vera; Barbados gooseberry mucilage; Chia mucilage; Linseed mucilage; Okra mucilage; Vegan; Vegetarian public